2012
DOI: 10.1167/iovs.11-8436
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Glaucoma on the Optical Attenuation Coefficient of the Retinal Nerve Fiber Layer in Spectral Domain Optical Coherence Tomography Images

Abstract: The measurements clearly demonstrated that the μ(att) of the RNFL decreased with increasing disease severity. The RNFL attenuation coefficient may serve as a new method to quantify glaucoma in SD-OCT images.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
81
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(84 citation statements)
references
References 38 publications
1
81
1
1
Order By: Relevance
“…Recent studies have shown that a decrease in RNFL reflectance occurs prior to thinning of the RNFL [5][6][7][8][9][10][11], and suggest that direct OCT measurement of RNFL reflectance may provide a powerful new method for the early detection of glaucoma. Although directional reflectance is a major source of variability for RNFL reflectance measurements [24][25][26], none of the in vivo studies took this into account.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies have shown that a decrease in RNFL reflectance occurs prior to thinning of the RNFL [5][6][7][8][9][10][11], and suggest that direct OCT measurement of RNFL reflectance may provide a powerful new method for the early detection of glaucoma. Although directional reflectance is a major source of variability for RNFL reflectance measurements [24][25][26], none of the in vivo studies took this into account.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Optical Coherence Tomography (OCT), which is widely used in clinical diagnosis of glaucoma, measures RNFL thickness by identifying the RNFL as a highly reflective layer under the retinal surface, with change of thickness used as a biomarker for axonal damage [1][2][3][4]. Recent studies of glaucomatous retinas reveal that a decrease of RNFL reflectance occurs prior to thinning of the RNFL [5][6][7][8][9][10][11]. Glaucoma damages retinal ganglion cells (RGC) and their axons [12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…22,23 Many studies solved the A-scan profile intensity variation by normalizing the RNFL signal intensity to the brightest layer in the OCT image, usually the RPE, as a preprocessing step before thickness measurement to reduce the variation. Those methods are simple and easy to implement, and can be applied to the entire OCT image.…”
Section: Discussionmentioning
confidence: 99%